Xenotransplantation in Healthcare: A Literature Review of Clinical Advances, Immunological Barriers, and Ethical Challenges - Thongwichian, Phonchai; Sari, Melsi Pita (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2025)
Background: The global shortage of donor organs remains a critical challenge in healthcare, driving the search for alternative strategies to reduce waiting list mortality. Xenotransplantation the transplantation of organs, tissues, or cells across species—has emerged as a promising solution. Advances in genetic engineering, immunological modulation, and tissue preservation have accelerated progress, yet clinical translation remains constrained by unresolved biological and ethical barriers.Objectives: This review aimed to systematically evaluate the current evidence on xenotransplantation, focusing on its safety, efficacy, immunological challenges, and societal implications, in order to assess its readiness for integration into clinical practice.Methods: A literature review was conducted in this study. PubMed and Scopus were searched for publications between January 2020 and August 2025. Eligible studies included clinical reports, preclinical experiments, mechanistic investigations, and survey-based studies addressing xenotransplantation. Data were extracted on study design, xenograft type, intervention details, and reported outcomes. Due to heterogeneity, results were synthesized narratively.Results: Twenty studies were included. Clinical reports demonstrated that genetically engineered pig organs could function in humans for several weeks, though rejection, coagulation dysregulation, and viral reactivation remain obstacles. Preclinical models in nonhuman primates and rodents confirmed prolonged graft survival with multigene donor modifications and costimulation blockade. Cellular approaches, including porcine islets and ovarian tissue grafts, showed promise in metabolic and reproductive medicine. Surveys revealed moderate public support but persistent concerns regarding safety and ethics.Conclusion: Xenotransplantation has progressed from experimental proof-of-concept to early clinical application. While advances in genetic editing, immunosuppression, and graft preservation are encouraging, clinical translation will require overcoming immunological and infectious barriers, alongside addressing societal and ethical considerations, to ensure safe and sustainable implementation in healthcare.